Sunlight-active Bi2O2(OH)(NO3)-AgBr photocatalyst for degradation of Rhodamine B (RhB) dye and disinfection of E. coli bacteria - Ruethaithip Dulyasucharit; Laksanawadee Saikhao; Sutthidech Preecharram; Nutthachai Prongmanee; Wipada Chaiyachet; Orapan Intharaksa; Suwat Nanan (OpenNano, 2025)
A sunlight-driven Bi2O2(OH)(NO3)-AgBr heterostructure photocatalyst (denoted as BiON-AgBr) was synthesized by a two-step route combining hydrothermal and chemical precipitation methods. Firstly, the pristine BiON was prepared, via two types of solvent, by using a hydrothermal method. In the case that water was used as a solvent, the BiON.W photocatalyst with a pine-like structure was obtained. However, by using mixed solvent (comprising ethanol: water of 20:80), the BiON.M photocatalyst with a flower-like morphology was achieved. Secondly, the binary BiON-AgBr heterostructure was then constructed using a chemical precipitation technique. Accordingly, the photocatalytic performance of the prepared BiON-AgBr photocatalyst was evaluated through the photodegradation of Rhodamine B (RhB) dye under natural sunlight irradiation. The synthesized BiON-AgBr photocatalyst still exhibits high photocatalytic efficiency, even after three consecutive cycles of use. Trapping experiment revealed that the superoxide anion radicals (•O₂⁻) play the most important role in RhB removal. The result suggested a Z-scheme mechanism based on AgBr/Ag/BiON. The formation of metallic silver (Ag0), upon sunlight illumination, was proved as the evidence shown in the XRD pattern of the used photocatalyst. The synergistic effect of the Z-scheme heterojunction and the surface plasmon resonance (SPR) of silver metal results in the considerable enhancement of the sunlight-driven photodegradation of RhB dye and the remarkable improvement of the disinfection of E. coli bacteria.